2015
DOI: 10.1007/1345_2015_6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Techniques for Tropospheric Wet Delay Retrieval Over South America and Surrounding Oceans

Abstract: Water vapour (WV) plays a fundamental role in several weather processes that deeply influence human activities. Satellite based radiometers, Ground based Global Navigation Satellite Systems (GNSS) and Numerical Weather Models (NWM) permit to obtain either measurements or estimates or forecasts of WV. This work presents a 2 years systematic comparison to address the agreement on the tropospheric wet delay retrieved by the three mentioned independent techniques over permanent stations belonging to SIRGAS (Sistem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Moreover, previous regional analysis of GNSS-derived water vapour in South America had narrow spatial and temporal coverage, employed GPS-only observations, and were focused on the validation of the methodology by comparison against radiosondes measurements (Sapucci et al, 2007), or radiosondes and satellite-based observations (Fernández et al, 2010). Another regional inter-technique comparison was performed by Calori et al (2015), using GPS-only observations, comprising about 30 sites, and spanning 2 years. Recently, a 1-year-long experiment employing an episodic but highly dense meteorological GNSS network in Amazonia studied water vapour-convection interactions in the tropics (Adams et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous regional analysis of GNSS-derived water vapour in South America had narrow spatial and temporal coverage, employed GPS-only observations, and were focused on the validation of the methodology by comparison against radiosondes measurements (Sapucci et al, 2007), or radiosondes and satellite-based observations (Fernández et al, 2010). Another regional inter-technique comparison was performed by Calori et al (2015), using GPS-only observations, comprising about 30 sites, and spanning 2 years. Recently, a 1-year-long experiment employing an episodic but highly dense meteorological GNSS network in Amazonia studied water vapour-convection interactions in the tropics (Adams et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The applied methodology requires observations of atmospheric pressure and temperature at each site, a topic that, in view of the limited in-situ observations, has been addressed through the use of reanalysis products for all SIRGAS-CON stations over the Latin America region (Calori et al, 2015). The uncertainty associated with the input variables depends on the method selected for the correction of pressure, based on the height difference between GNSS sites and MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Latin America has a permanent GNSS observation network, SIRGAS-CON (Geocentric Reference System for the Americas-Continuous GNSS network), which, by the end of 2017, already exceeded 420 operational stations (Cioce et al, 2018). It densifies the International Terrestrial Reference Frame (ITRF) in Latin America (Sanchez et al, 2015;Brunini et al, 2012), and it can be used for atmospheric monitoring, as shown in Brunini et al (2008) and Calori et al (2015). The Integrated Water Vapor (IWV) is the total amount of water vapor present in a vertical atmospheric column over a specific site, such as a GNSS site.…”
Section: Introductionmentioning
confidence: 99%